Communication/education in Latin America: an approach from institutions and technology in education - González Sierra, Darwin (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: This article offers an approach to the academic field of communication/education in Latin America. It examines the role of three institutions on the emergence and development of this field in some intellectual circles of the continent. These institutions are as follows: the United Nations Educational, Scientific and Cultural Organization (UNESCO); the Latin American Association of Communication Researchers (ALAIC), and the International Center for Higher Studies in Communication for Latin America (CIESPAL). Originality/contribution: This approach contributes to the reflection on new technologies in educational spaces in recent years. We take into account that this relationship is treated as a location of enunciation by the communication/education domain. Method: A documentary review of the institutions mentioned above with conceptual locations of sociology used as a research tool. Strategies/information gathering: archival research based on relevant documents from the three institutions. The texts were selected in order of importance from the state of the art and the consolidation of documentary sources.   Conclusions: The present work updates discussions proper to the field of education and information and communication technologies, beyond instrumental reductionisms. These discussions offer a perspective on the intrinsic problems of teaching, on the use of technologies in schools, and also on possible research topics within this framework of analysis.